Implementasi Metode Arabic Game: Tebak Kata Dalam Pembelajaran Maharah Kalam - Lathifatul Insaniyah , Anyes; Munawaroh, Nikmatul (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
This research aims to determine the implementation of the Arabic game method in Maharah Kalam learning as well as the supporting and inhibiting factors at Public High Scholl 1 Banyuwangi. The research method uses qualitative descriptive research. Data collection techniques were carried out by means of observation, interviews and documentation. Meanwhile, data analysis uses interactive models by analyzing data, processing data, and drawing conclusions from the data obtained as well as describing and reporting what happens in the field using descriptive qualitative analysis techniques. From the research results it was found that the Arabic game method used was the word guessing method, namely by demonstrating the method, the teacher divided the students into several groups then the teacher showed a word to the student at the front, then he demonstrated it to a friend in front of him, if he could not demonstrate it. The friend behind them is replaced, and if there is a friend who can answer correctly then he is the one who demonstrates it, and so on, the group that manages to collect the most words in approximately 3 minutes is the winner. Supporting and inhibiting factors for learning Arabic are triggered by several factors, namely supporting factors such as teacher educators, motivation and the methods used. Apart from that, there are inhibiting factors such as students' different backgrounds, learning difficulties, environmental factors, and psychological factors.